Expression of expanded GGC repeats within NOTCH2NLC causes cardiac dysfunction in mouse models - Yongcheng Pan; Ying Jiang; Juan Wan; Zhengmao Hu; Hong Jiang; Lu Shen; Beisha Tang; Yun Tian; Qiong Liu (Cell & Bioscience, 2023)
Abstract Background Neuronal intranuclear inclusion disease (NIID) is a rare neurodegenerative disorder characterized by widespread intranuclear inclusions in the nervous system as well as multiple visceral organs. In 2019, expanded GGC repeats within the 5′ untranslated region of the NOTCH2NLC gene was identified as the causative factor. NIID is a heterogeneous disorder with variable clinical manifestations including cognitive impairment, cerebellar ataxia, parkinsonism, paroxysmal symptoms, autonomic dysfunction, and muscle weakness. Although NIID primarily affects the central and peripheral nervous systems, growing evidence suggests potential cardiac abnormalities in NIID. However, the link between expanded GGC repeats within NOTCH2NLC and cardiac dysfunction remains uncertain. Results In this study, we utilized two transgenic mouse models, expressing NOTCH2NLC-(GGC) 98 ubiquitously or specifically in cardiomyocytes, and identified p62 (also known as sequestosome 1, SQSTM1)-positive intranuclear NOTCH2NLC-polyG inclusions in cardiomyocytes in two mouse models. We observed that both models exhibited cardiac-related pathological and echocardiographic changes, albeit exhibiting varying degrees of severity. Transcriptomic analysis revealed shared downregulation of genes related to ion channels and mitochondria in both models, with the cardiomyocyte-specific mice showing a more pronounced downregulation of mitochondria and energy metabolism-related pathways. Further investigations revealed decreased expression of mitochondria-related genes and electron transport chain activity. At last, we conducted a retrospective review of cardiac-related examination results from NIID patients at our hospital and also identified some cardiac abnormalities in NIID patients. Conclusions Our study provided the first in vivo evidence linking GGC repeat expansions within NOTCH2NLC to cardiac abnormalities and highlighted the contribution of mitochondrial dysfunction in the development of cardiac abnormalities.